Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) with intracranial Epstein–Barr virus infection: A Case Report. Issue 46 (November 2016) - Ma, Yue; Sun, Xiaolong; Li, Wen; Li, Yi; Kang, Tao; Yang, Xiai; Jiang, Wen
Abstract: Background: Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) is an inflammatory disorder in the central nervous system (CNS) with distinct clinical, radiological, and pathological features. The pathophysiology of CLIPPERS still remains unclear and the reports are quite few. Although the radiological lesions were reported to be located predominantly in the pons, brachium pontis, and cerebellum, other adjacent structures such as the white matter and spinal cord were very recently reported as involved regions in CLIPPERS. In this study, we report a case of CLIPPERS presenting with intracranial Epstein–Barr virus (EBV) infection and diffuse white matter involvement. Case summary: A 37-year-old male was diagnosed with mediastinal Hodgkin's lymphoma (lymphocyte predominance type) at the age of 26, and then obtained complete remission after treatment and remained free of relapse for 11 years. He was admitted with 7 months' history of mental disorder, and 20 days' history of gait and limb ataxia, dysphagia, and cough. The diagnosis of CLIPPERS was established based on the findings of punctate and nodular enhancing lesions in the bilateral pons, the basal ganglia, the mid-brain, the pontine brachium, and diffuse white matter in magnetic resonance imaging (MRI), together with CD3 + T-lymphocytic inflammatory infiltration in perivascular and parenchymal area revealed by bilateral parietal lobe brain biopsy. Also, our patient exhibited a good response to steroid therapy and remained free of relapse for 5 months. Importantly, we found intracranial Epstein–Barr virus infection in this patient. Conclusion: CLIPPERS might be an autoimmune disorder, and intracranial EBV-infection raises the possibility that EBV-associated autoimmunity is associated with CLIPPERS pathogenesis.